The Transcriptional Landscapes and Key Genes in Brain Arteriovenous Malformation Progression in a Venous Hypertension Rat Model Revealed by RNA Sequencing - Li S; Tao W; Huang Z; Yan L; Chen B; Zeng C; Chen F (Dove Medical Press, 2022)
Shifu Li, Wengui Tao, Zheng Huang, Langchao Yan, Bo Chen, Chudai Zeng, Fenghua Chen Department of Neurosurgery, Xiangya Hospital, Central South University, Changsha, People's Republic of ChinaCorrespondence: Fenghua Chen, Department of Neurosurgery, Xiangya Hospital, Central South University, Changsha, 410008, Hunan, People's Republic of China, Email xyswcfh@csu.edu.cnBackground: Brain arteriovenous malformations (bAVM) are abnormal vascular lesions characterized by direct connections between arteries and veins without an intervening capillary bed. The primary goal for brain AVM treatment is to prevent rupture and hemorrhage; however, the underlying molecular mechanisms are still unknown.Methods: We constructed venous hypertension (VH) rat model with end-to-end anastomosis of the proximal left common carotid artery and the left distal external jugular vein. Thirty-eight adult rats were randomly assigned to four groups: the 0-week (n=5), the 1-week VH group (n=12), the 3-week VH group (n=9), and the 6-week VH group (n=12). We measured the hemodynamics and diameter of the arterialized veins. An RNA sequencing of arterialized veins was conducted, followed by comprehensive bioinformatics analysis to identify key genes and biological pathways involved in VH progression. The candidate genes from RNA-Seq were validated by RT-qPCR and immunostaining in human tissues.Results: We observed high-flow and low resistance characteristics in VH models. A total of 317 upregulated and 258 downregulated common genes were consistently differentially expressed during VH progression. Thirteen co-expression modules were obtained by WGCNA analysis, and 4 key modules were identified. Thirteen genes: Adamts8, Adamtsl3, Spon2, Adamtsl2, Chad, Itga7, Comp, Itga8, Bmp6, Fst, Smad6, Smad7, Grem1, and Nog with differential expressions were identified using the density of maximum neighborhood component (DMNC) algorithm in Cytohubba. The expression of five potential genes (Adamts8, Adamtsl3, Spon2, Adamtsl2, Itga8) were increased in RT-qPCR, while in human bAVM tissue, the protein levels of Adamtsl2 and Itga8 were significant elevated and Spon2 and Adamtsl3 were decreased.Conclusion: The identified gene networks of Adamtsl3, Spon2, Adamtsl2, and Itga8 provided key genes for further intervention.Graphical Abstarct: Keywords: WGCNA, xCells, focal adhesion, vascular microenvironment, bioinformatics